The impact of trade liberalisation on adjustment of regional wages in Estonia - Grigori Fainstein (European Regional Science Association (ERSA), 2005)
The purpose of this paper is twofold. First, we aim at analysing the development of regional specialisation in Estonia since the beginning of trade liberalisation and integration into the EU in the early 1990s. Second, given the patterns of developments in specialisation, we analyse how trade liberalisation has affected structure of regional wages. The main data used in this study consist of a panel of 5 geographic regions aggregated at the NUTS3 level by the EU classification. For every region we calculated indices of regional industrial specialisation in 1990-2002. The indices are based on data for employment in manufacturing industries classified by two-digit NACE standard (total of 13 industries). The impact of integration with EU on regional development is based on the data for average wages in industry in regions at NUTS IV level (15 administrative units of Estonia). The analysis of industrial specialisation in Estonian NUTS III regions showed that the level of specialisation has increased on average by 1-1.5% a year. As for transition economy time is a fair proxy to integration, we may conclude that initial stages of establishing closer economic relations with EU and voluminous target investments into the regions stimulated specialisation. Econometric analysis of relationship between relative regional wages and distance to the capital suggests an explanation consistent with new economic geography hypothesis. Surprisingly, in spite of small size of Estonian territory, distance have essensial effect on variations in regional wages. Our estimates show that integration with EU and trade liberalisation minimises negative impact of distance.
Keywords: 330